Using Real-Life Data to Strengthen the Education of Pharmacy Technician Students: From Student to Research Assistant - Bjarke Abrahamsen; Rikke Nørgaard Hansen; Marianne Bjørn-Christensen; Tina Druskeit; Charlotte Rossing (MDPI AG, 2020)
This commentary is based on the experience of teaching and observations of how pharmacy technician students can expand their perspective on patient safety by using real-life student-gathered patient data collected from community pharmacies. Pharmacy technicians in Denmark work extensively with counselling on the safe and efficient use of medications. Final-year pharmacy technician students can take the elective course in Clinical Pharmacy in Community Pharmacy, which targets the students who wish to work in depth with patient communication and quality assurance in counselling. One assignment that forms part of the course is for students to collect data about patients' beliefs about medications. Teachers' observations suggest that when students gather and work with their own data, they change their perspective on patients' beliefs about medications. It also strengthens the students' awareness of their responsibility for ensuring patient safety and contributes valid data to research in pharmacy practice.